Improving Mathematics Learning Outcomes using Ice Cream Stick Concrete Media in Grade 4 Elementary School Students - Rahmah, Wahyu Putri; Fuad, A. Jauhar (Noumerico: Journal of Technology in Mathematics Education, 2023)
The background of this research is the low mathematics learning outcomes of students in grade 4 at 3 Kelutan State Elementary School. This is because learning uses the lecture method so students feel bored and less enthusiastic about participating in learning. This study aims to improve the results of learning mathematics material multiplication arithmetic operations after learning is applied using concrete ice cream stick media. This study used the Classroom Action Research method with 2 cycles. The stages of the research carried out were planning, implementing, observing, and reflecting. The research subjects were 4th-grade students at 3 Kelutan State Elementary School Ngronggot Nganjuk with a total of 15 students. The data analysis technique used is descriptive quantitative by collecting data on learning outcomes carried out in each cycle. The indicator of success in this study is if 75% of students master the material with a minimum completeness criterion of 70. The results of the study show that concrete media can improve mathematics learning outcomes on multiplication arithmetic operations for students in grades 4 at 3 Kelutan State Elementary School. In cycle 1, 40% of students have achieved Minimum Completeness Criteria with an average score of 57.33. Then in cycle II, 80% of students achieved minimum completeness criteria with an average value of 79.33. So it can be concluded that the concrete media of Ice Cream Sticks can improve the mathematics learning outcomes of students in grade 4 at 3 Kelutan State Elementary School.